Prior Heavy-Intensity Exercise's Enhancement of Oxygen-Uptake Kinetics and Short-Term High-Intensity Exercise Performance Independent of Aerobic-Training Status - Carita, Renato A. C. [UNESP]; Greco, Camila C. [UNESP]; Denadai, Benedito S. [UNESP] (Human Kinetics Publ Inc, 2015)
Prior high-intensity exercise can improve exercise performance during severe-intensity exercise. These positive alterations have been attributed, at least in part, to enhancement of overall oxygen-uptake (VO2) kinetics. Purpose: To determine the effects of prior heavy-intensity exercise on VO2 kinetics and short-term high-intensity exercise performance in individuals with different aerobic-training statuses. Methods: Fifteen active subjects (UT; VO2max = 43.8 +/- 6.3 mL.kg(-1).min(-1)) and 10 well-trained endurance cyclists (T; VO2max = 66.7 +/- 6.7 mL.kg(-1).min(-1)) performed the following protocols: an incremental test to determine lactate threshold and VO2max, 4 maximal constant-load tests to estimate critical power, and two 3-min bouts of cycle exercise, involving 2 min of constant-work-rate exercise at severe intensity followed by a 1-min all-out sprint test. This trial was performed without prior intervention and 10 min after prior heavy-intensity exercise (ie, 6 min at 90% critical power). Results: The mean response time of VO2 was shortened after prior exercise for both UT (30.7 +/- 9.2 vs 24.1 +/- 7.2 s) and T (31.8 +/- 5.2 vs 25.4 +/- 4.3 s), but no group-by-condition interaction was detected. The end-sprint performance (ie, mean power output) was improved in both groups (UT similar to 4.7%, T similar to 2.0%; P < .05) by prior exercise. Conclusion: The effect of prior heavy-intensity exercise on overall VO2 kinetics and short-term high-intensity exercise performance is independent of aerobic-training status.
Keywords: sport; critical power; VO2